Bibliography: Recent Publications in Canadian Labour History = Bibliographie : Travaux récents en histoire des classes populaires canadiennes (30, Fall 1992) - Lonardo, Michael; Sweeney, Robert C. H. (Labour / Le Travail, 1992)
Compilation of recent English/French publications on Canadian labour history that emphasize the period 1800-1975. Materials pertaining to the post-1975 period may also be included, although more selectively. See the database, Canadian Labour History, 1976-2009, published at Memorial University of Newfoundland.
Keywords: BIBLIOGRAPHY (Documentation); Labor